Evaluation of hydrolytic degradation of bionanocomposites through fourier transform infrared spectroscopy - Silva,Raquel do Nascimento (2018)
Abstract Studies about in vitro biodegradation of polymers have grown considerably due to the wide application of biodegradable polymers in biomedical areas. The objective of this study was to prepare bionanocomposites films of PHB, PEG, and organoclays by solution intercalation, and to evaluate the morphology, structure, hydrolytic degradation through FTIR and the calculation of carbonyl content. The results showed that bionanocomposites displayed intermediated dispersion of the filler, the polymer chains were intercalated into the organoclay layers and was observed some degree of exfoliation. There was an influence of PEG and of the clay on the degradation of the polymer, this fact was observed due to the decrease in the intensity of PHB carbonyl band in the region around 1275 cm-1, affecting the amorphous and crystalline regions of the polymer. This reduction can be associated with the increase in hydrophilicity of the polymer caused by the presence of the PEG and clay, suggesting the possibility of increasing the biodegradability of the pure polymer. In future research, there will be made characterizations to know if these materials can be used in medical devices.